Impact of microstructure evolution on the corrosion behaviour of the Ti–6Al–4V alloy welded joint using high-frequency pulse wave laser - Li, Zhen; Zhao, Wei; Xiao, Guangchun; Chen, Kai; Zhang, Hui; Guo, Ning; Xu, Lianyong (Journal of materials research and technology, 2023)
In this work, a high-frequency pulsed laser-welding process was successfully implemented to fabricate a Ti–6Al–4V alloy butt joint. The microstructure of each zone of the welded joint was systematically characterized by carrying out scanning electron microscopy and electron backscatter diffraction measurements. In addition, the corrosion resistance of the welded joint was tested using traditional electrochemical and local electrochemical methods, while the main factors affecting corrosion resistance and the mechanism of the galvanic corrosion were also thoroughly investigated. From the acquired results, it was demonstrated that the α′ martensitic phases constituted the microstructure in the fusion zone (FZ), where the grain size, grain orientation, and misorientation distribution of the different zones varied, and the α′ martensitic and bulk α covered the heat-affected zone (HAZ). The corrosion resistance in the HAZ was slightly better than that in the base material, and both were worse than that of the FZ, which was related to the phase type. In addition, the corrosion current density values of FZupper were about 1/4.6 and 1/2.6 those of FZmiddle and FZdown, respectively, which was attributed to differences in the grain size and grain orientation. The FZ was protected as a cathode during galvanic corrosion, which is of great importance for ensuring the service life of the component during practical applications.